Second International Conference on Future Generation Communication Technologies (FGCT 2013) 2013
DOI: 10.1109/fgct.2013.6767188
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of self-tagging during conversational chat in multilingual gaming simulation

Abstract: A multilingual gaming simulation is suggested as the basis of an experiment by which we discuss complex problems such as global civics or environmental problems. Assigning tags is a very important way to analyze this experiment. However, assigning tags has a cost that is too large for analysts. In this study, we suggest and introduce a method for participants to voluntarily self-tag, focusing on gamification and crowdsourcing. As a result, we verified that it is possible for analysts to reduce the tagging cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Y. Lee et al, 2013;Y. Liu, Alexandrova, Nakajima et al, 2011;Machnik et al, 2015;Martella et al, 2015;Massung et al, 2013;Melenhorst et al, 2015;Nose and Hishiyama, 2013;Packham and Suleman, 2015;Pothineni et al, 2014;Prandi et al, 2016;Preist et al, 2014;Prestopnik and Tang, 2015;Roengsamut et al, 2015;Runge et al, 2015;Saito et al, 2014;Simões and De Amicis, 2016;Snijders et al, 2015;Sørensen et al, 2016;Talasila et al, 2016;Tinati et al, 2016;Vasilescu et al, 2014 37 33.6 Empirical studies with no results on how gamification works in crowdsourcing Bentzien et al, 2013;Brenner et al, 2014;Brito et al, 2015;Cao et al, 2015;Chamberlain, 2014;Cucari et al, 2016;Deng et al, 2016;Dos Santos et al, 2015;Harris, 2014;He et al, 2014;Inaba et al, 2015;Kacorri et al, 2014;Kurita et al, 2016;Lauto and Valentin, 2016;Lessel et al, 2015;Mason et al, 2012;Nagai et al, 2014;Nunzio et al, 2016;Riegler et al, 2015;…”
Section: Descriptive Informationmentioning
confidence: 99%
“…Y. Lee et al, 2013;Y. Liu, Alexandrova, Nakajima et al, 2011;Machnik et al, 2015;Martella et al, 2015;Massung et al, 2013;Melenhorst et al, 2015;Nose and Hishiyama, 2013;Packham and Suleman, 2015;Pothineni et al, 2014;Prandi et al, 2016;Preist et al, 2014;Prestopnik and Tang, 2015;Roengsamut et al, 2015;Runge et al, 2015;Saito et al, 2014;Simões and De Amicis, 2016;Snijders et al, 2015;Sørensen et al, 2016;Talasila et al, 2016;Tinati et al, 2016;Vasilescu et al, 2014 37 33.6 Empirical studies with no results on how gamification works in crowdsourcing Bentzien et al, 2013;Brenner et al, 2014;Brito et al, 2015;Cao et al, 2015;Chamberlain, 2014;Cucari et al, 2016;Deng et al, 2016;Dos Santos et al, 2015;Harris, 2014;He et al, 2014;Inaba et al, 2015;Kacorri et al, 2014;Kurita et al, 2016;Lauto and Valentin, 2016;Lessel et al, 2015;Mason et al, 2012;Nagai et al, 2014;Nunzio et al, 2016;Riegler et al, 2015;…”
Section: Descriptive Informationmentioning
confidence: 99%
“…However, the authors investigated this only in the short-term and indicated that financial rewards in comparison to gamification may reduce the participation in the long-term. [28], [30], [35], [36], [40], [41], [43], [44], [45], [47], [48], [49], [52], [53], [55] [3], [27], [33], [36], [44], [52] [9], [10], [16], [22], [30], [41], [42], [46], [47] [23], [35] 1 , [40], [53], [55] [45], [49] 22 leaderboards/ rankings [3], [27], [28], [33], [36], [52] [4], [9], [10], [16], [22], [42], [46], [47] [23], [35], [40], …”
Section: How Gamification Is Used?mentioning
confidence: 99%
“…Most studies that directly compared a gamified and non-gamified approach (e.g. [10,16,28,33,36,40,44,53]) report several positive effects, like the increase of (long-term [36]) engagement [10,28,33,36,44,53], quality of the output [10,16,36] and reduction in cheating compared to traditional paid CS [10]. However, gamification does not necessarily lead to an increase in participation.…”
Section: Does Gamification Work?mentioning
confidence: 99%
See 2 more Smart Citations